An Analysis of Students' Reading Comprehension Difficulties in English Texts at SMK Swasta Pancadharma Padangsidimpuan - pulungan, Monika hapni; Maharani; Meidipa, Lisa Fitri (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2023)
This research investigates the reading comprehension difficulties faced by students at SMK Swasta Pancadharma Padangsidimpuan, focusing on identifying the most challenging aspects of understanding English texts. The study employs a descriptive qualitative methodology, encompassing observation, questionnaires, and tests to gather data. The participants include 30 tenth-grade students from the administration major, chosen through cluster sampling. The research findings indicate that students primarily struggle with vocabulary deficiencies, which hinder their ability to comprehend main ideas and supporting details in texts. Additionally, the length of English texts exacerbates these comprehension challenges, causing disinterest and difficulties in understanding and summarizing the content. The study identifies that the highest difficulty lies in finding supporting ideas, with 71% of students unable to accurately answer related questions. Other significant difficulties include answering detailed questions (44%), understanding antonyms (41%), and interpreting words in context (40%). The least challenging aspect was finding the main ideas (31%). The research suggests that enhancing vocabulary knowledge and employing effective reading strategies can significantly improve students' reading comprehension skills. It recommends that teachers adopt more creative and engaging teaching methods and utilize various media to assist students in mastering vocabulary. For students, the study emphasizes the importance of active participation and motivation in learning. Future researchers are encouraged to explore the use of online media and broader participant groups to further understand and address reading comprehension challenges. By addressing these issues, the study aims to improve reading comprehension among students, thereby enhancing their overall proficiency in English.